Suplementação de unha-de-gato (Uncaria tomentosa) em dietas para tilápias-do-Nilo e acará-bandeira (Pterophyllum scalare) - Cala Delgado, Daniel Leonardo [UNESP] (2015)
Cat's claw (Uncaria tomentosa) is an Amazonian plant that presents anti-inflammatory properties. Previous studies have shown an increase in the productive performance of Nile tilapia; however, fish presented liver alterations. This study aimed to evaluate the performance and toxicological aspects in Nile tilapia and freshwater angelfish fed diets supplemented with cat's claw. In the study with Nile tilapia were tested supplementation levels of 0; 150; 300; 450 mg of cat's claw/Kgof feed, and the assessment of Nile tilapia was in a randomized block design (weight) with four replications. In the initial assessment, there were two biometrics (30 days and 60 days) to evaluate growth performance, collection of blood and organs (liver, kidney, spleen). In the study with angelfish, were studied levels of 0; 75; 150; 300; 450 mg of cat's claw/Kg of diet in a completely randomized design.For the analysis of growth performance and collection of organs were collected every 30 days for 5 months, and in the last month fish were submitted to simulations of transport for 24 hours. After that, they were evaluated blood glucose, mortality and water quality parameters. In the study with Nile tilapia, at 30 days, fish presented a reduction in feed mean intake and feed conversion in the groups fed diets containing cat's claw. Total protein and globulin were higher in the group fed 450 mg/Kg. Other parameters did not differ (p> 0.05) between treatments. At 60 days,Nile tilapia supplemented with the plant did not show differences in growth performance and blood countcompared to the control group. At 30 days there was no difference between treatments for blood glucose, but this same parameter at 60 days was lower in the treatment 450 mg/kg compared with control group.In the test of hepatic functionality, the levels of aspartate transaminase (AST), total protein (TP) and globulin were higher in the groups supplemented with cat's claw, as well as liver ...